Diagnosing COVID-19; towards a feasible COVID-19 rule-out protocol. Issue 2 (4th March 2022) - De Clercq, J.; Malfait, T.; Malfait, S.; Boelens, J.; Coorevits, L.; Padalko, E.; Vandendriessche, S.; Verhasselt, B.; Morbée, L.; Bauters, F.; Hertegonne, K.; Stevens, D.; et al.
ABSTRACT: Introduction: We present the results of the COVID-19 rule-out protocol at Ghent University Hospital, a step-wise testing approach which included repeat NFS SARS-CoV-2 rRT-PCR, respiratory multiplex RT-PCR, low-dose chest CT and bronchoscopy with BAL to confirm or rule-out SARS-CoV-2 infection in patients admitted with symptoms suggestive of COVID-19. Results: Between 19 March 2020 and 30 April 2020, 455 non-critically ill patients with symptoms suspect for COVID-19 were admitted. The initial NFS for SARS-CoV-2 rRT-PCR yielded 66.9%, the second NFS 25.4% and bronchoscopy with BAL 5.9% of total COVID-19 diagnoses. In the BAL fluid, other respiratory pathogens were detected in 65% (13/20) of the COVID-19 negative patients and only in 1/7 COVID-19 positive patients. Retrospective antibody testing at the time around BAL sampling showed a positive IgA or IgG in 42.9 % of the COVID-19 positive and 10.5% of the COVID-19 negative group. Follow-up serology showed 100% COVID-19 positivity in the COVID-19 positive group and 100% IgG negativity in the COVID-19 negative group. Conclusion: In our experience, bronchoscopy with BAL can have an added value to rule-in or rule-out COVID-19 in patients with clinical and radiographical high-likelihood of COVID-19 and repeated negative NFS testing. Furthermore, culture and respiratory multiplex PCR on BAL fluid can aid to identify alternative microbial etiological agents in this group. Retrospective analysis of antibody development in this selected group of patients suggests that the implementation of serological assays in the routine testing protocol will decrease the need for invasive procedures like bronchoscopy.